Peningkatan Keterampilan Menulis Puisi melalui Strategi Reviewing a Film Pada Siswa Kelas X IPS 3 SMA Negeri 1 Kalasan - Dewi Umi Rohmatun Dewi Umi Rohmatun; Denik Wirawati; Pipit Ristiana Anggraini (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2023)
The study aims to imprve the learning process and writing skills of poetry texts for class X Social 3 SMAN 1 Kalasan in the academic year 2022/2023. The learning process and writing skills of poetry are improved through the application of the strategy reviewing a film. This type of research is a classroom action research conducted by the writer with the teacher as well as collaborator in two cycles. The subject of this study were students of class X Social 3 SMAN 1 Kalasan. Data collection was carried out by observation, interviews, filling out questionnaires amd written tests. The results of this study indicate that the implementation of the reviewing a film strategy in the learning process of writing poetry texts, especially in tems of skills and student activity whwn responding to questions about doing exercises or assignment 72,53%, and taking notes has increased to 88,75% in two cycles. Then in terms of learning outcomes writing poetry texts can improve skills as evidenced by the competency test. In the first cycle the average obtained was 78,33 and increased again to 88,17 in the second cycle. So, it can be concluded that the strategi of reviewing a film is effective in improving the learning process and writing skills of student class X Social 3 SMAN 1 Kalasan.